Biogenic silver nanoparticles based on trichoderma harzianum: Synthesis, characterization, toxicity evaluation and biological activity - Guilger, Mariana; Pasquoto-Stigliani, Tatiane; Bilesky-Jose, Natália; Grillo, Renato; Abhilash, P. C.; Fraceto, Leonardo Fernandes [UNESP]; De Lima, Renata (Springer Nature, 2017)
White mold is an agricultural disease caused by the fungus Sclerotinia sclerotiorum, which affects important crops. There are different ways of controlling this organism, but none provides inhibition of its resistance structures (sclerotia). Nanotechnology offers promising applications in agricultural area. Here, silver nanoparticles were biogenically synthesized using the fungus Trichoderma harzianum and characterized. Cytotoxicity and genotoxicity were evaluated, and the nanoparticles were initially tested against white mold sclerotia. Their effects on soybean were also investigated with no effects observed. The nanoparticles showed potential against S. sclerotiorum, inhibiting sclerotia germination and mycelial growth. Nanoparticle characterization data indicated spherical morphology, satisfactory polydispersity and size distribution. Cytotoxicity and genotoxicity assays showed that the nanoparticles caused both the effects, although, the most toxic concentrations were above those applied for white mold control. Given the potential of the nanoparticles against S. sclerotiorum, we conclude that this study presents a first step for a new alternative in white mold control.